Sosialisasi Gerakan Membentuk Keluarga Sehat Dan Sejahtera Pada Masyarakat - Fani Farhansyah (AMMA : Jurnal Pengabdian Masyarakat, 2024)
A family can be declared healthy if it meets the family indicators set by the Indonesian Ministry of Health (2016) regarding the Healthy Indonesia Program with a family approach (PIS-PK). The method of community service activities is carried out by providing socialization to the community about understanding the importance of forming a healthy and prosperous family. The socialization method is carried out in the form of lectures, discussions and questions and answers to the community. Community service activities were carried out on Friday, June 28, 2024 at the Ciputra Pekanbaru Mall which was attended by various groups of people. This PKM activity began with healthy exercise with the community. After that, it was continued with the delivery of socialization material to the community regarding understanding the importance of forming a healthy and prosperous family. During the delivery of the socialization material, the participants or the community were very enthusiastic in listening to the material. It is hoped that this activity can provide education to the community about the importance of building a healthy family. This community service activity went well with the support of all groups.